Bridging the gap: The nexus of sustainability innovation, knowledge sharing, and green volunteerism for manufacturing entrepreneurial triumph - Chia-Yang Lin; Ka Yin Chau; Massoud Moslehpour (Journal of Innovation & Knowledge)
The present study captures the essential role of environmental and social innovation driving success of entrepreneurs in the presence of knowledge sharing culture as a mediator and green volunteer behaviour as a moderator. With a particular focus on Vietnam, the study selects manufacturing SMEs because of their bigger role in Vietnam's economy. Since, SMEs foster innovation which is crucial for sustainability and competitive advantage. Therefore, it is imperative to assess the relationship in SMEs context. With quantitative approach, the study collected data from Vietnam's manufacturing SMEs, examining how social innovation focusing on societal needs; environmental innovation emphasizing on environmentally friendly practices contribute to entrepreneurial success. The study used PLS methodology to assess the linkage among variables. Outcomes of the study reveal that both kind of innovations are crucial for entrepreneurial success, however, their significance remarkably enhances when knowledge sharing culture mediates the relationship. This partially mediate role of knowledge sharing culture demonstrates that organizational culture builds on knowledge sharing idea promotes innovative idea, encouraging entrepreneurs to cultivate collaborative environment that further improves the efficacy of innovative ideas. The outcomes also indicated that green volunteer behaviour insignificantly moderates among knowledge-sharing culture and entrepreneurial success. The absence of moderation indicates that even with a focus on environmental goal, green volunteer behavior seems to have no direct alignment with prompt business goals of entrepreneurial success. Hence, the chances are greater that it may dilute the effect of knowledge sharing culture on environmental success.